Design, characterization and evaluation of a new 99mTc-labeled folate derivative with affinity towards folate receptor. (15th April 2023) - Das, Soumen; Sakhare, Navin; Kumar, Dheeraj; Mathur, Anupam; Mirapurkar, Shubhangi; Sheela, M.; Mohanty, Bhabani; Chaudhari, Pradip; Chakraborty, Sudipta
Graphical abstract: Abstract: Folate receptors (FRs) are known to be over-expressed in several human malignancies and therefore serve as an important target for small radiolabeled folate derivatives for non-invasive imaging of tumor, which is an important tool for future treatment recourse. In the present article, we report the synthesis of a new 99m Tc-labeled radiotracer for the aforementioned application following the well-established 99m Tc-'4+1' chemistry. Formation of the desired [ 99m Tc]Tc-complex with >95% radiochemical purity was confirmed by radio-HPLC and its structure was ascertained by characterizing a natural rhenium analogue of the said complex. Although the ligand exhibited a weaker affinity towards FRs compared to native folic acid (IC50 8.09 µM vs 29.46 nM), the 99m Tc-labeled complex was found to bind folate receptor-positive KB cells with high specificity (∼90%). Similar studies in a folate receptor negative cell line viz. A549 further corroborated the receptor-specificity of the synthesized complex. In vivo studies in KB tumor xenograft showed moderate uptake of ∼2.6% upto 3 h post-injection with high specificity (∼80%). The favorable features observed warrant further screening of the current design towards achieving an improved molecular probe for the said application.